Does financial development reduce CO2 emissions in Malaysian economy? / Irdina Adrin - Adrin, Irdina (2022)
In the country of Malaysia, this study deals with the question whether financial development reduces C02 emissions or not in case of Malaysia. The limits testing technique to cointegration between variables is used for this purpose. We show that C02 emissions, financial development, economic growth, foreign direct investment, and trade all have strong long-term correlations. Financial development also appears to lower C02 emissions, according to the findings. C02 emissions are exacerbated by increased energy usage and economic growth. The latest research paper found with similar executions results that the Granger causality analysis demonstrates the feedback hypothesis between financial development and C02 emissions, as well as between C02 emissions and economic growth was in 2013. There is no similar research paper that is more updated to this current year, however in 2020, there is a paper that conducted similarly which examines the impacts of financial development on sectoral carbon emissions (C02) for environmental quality in Malaysia. Conclude that in general, financial development increases C02 emissions and reduces environmental quality in Malaysia. The dependant variable for this research study is C02 Emissions while the independent variables are financial development, economic growth, foreign direct investment, and trade. This study will be from the year 1971 to this recent year of 2020. The variables examined in this study (Financial Development, Economic Growth, Foreign Direct Investment and Trade) showed a similar linkage on the C02 Emissions that has been explored in previous research. However, there is only one independent variable that has a significant impact on the C02 Emissions, and that is the Financial Development, which has a positive relationship. Others, such as Economic Growth and Foreign Direct Investment, have a negative and insignificant influence on the C02 Emissions, whereas Trade has a positive and insignificant impact